Basement membrane stiffening promotes retinal endothelial activation associated with diabetes. Issue 2 (6th October 2015) - Yang, Xiao; Scott, Harry A.; Monickaraj, Finny; Xu, Jun; Ardekani, Soroush; Nitta, Carolina F.; Cabrera, Andrea; McGuire, Paul G.; Mohideen, Umar; Das, Arup; Ghosh, Kaustabh
Abstract : Endothelial activation is a hallmark of the high‐glucose (HG)‐induced retinal inflammation associated with diabetic retinopathy (DR). However, precisely how HG induces retinal endothelial activation is not fully understood. We hypothesized that HG‐induced upregulation of lysyl oxidase (LOX), a collagen‐cross‐linking enzyme, in retinal capillary endothelial cells (ECs) enhances subendothelial basement membrane (BM) stiffness, which, in turn, promotes retinal EC activation. Diabetic C57BL/6 mice exhibiting a 70 and 50% increase in retinal intercellular adhesion molecule (ICAM)‐1 expression and leukocyte accumulation, respectively, demonstrated a 2‐fold increase in the levels of BM collagen IV and LOX, key determinants of capillary BM stiffness. Using atomic force microscopy, we confirmed that HG significantly enhances LOX‐dependent subendothelial matrix stiffness invitro, which correlated with an 2.5‐fold increase in endothelial ICAM‐1 expression, a 4‐fold greater monocyte—EC adhesion, and an 2‐fold alteration in endothelial NO (decrease) and NF‐κB activation (increase). Inhibition of LOX‐dependent subendothelial matrix stiffening alone suppressed HG‐induced retinal EC activation. Finally, using synthetic matrices of tunable stiffness, we demonstrated that subendothelial matrix stiffening is necessary and sufficient to promote EC activation. These findings implicate BM stiffening as a critical determinant of HG‐induced retinal EC activation and provide a rationale for examining BM stiffness and underlying mechanotransduction pathways as therapeutic targets for diabetic retinopathy.—Yang, X., Scott, H. A., Monickaraj, F., Xu, J., Ardekani, S., Nitta, C. F., Cabrera, A., McGuire, P. G., Mohideen, U., Das, A., Ghosh, K. Basement membrane stiffening promotes retinal endothelial activation associated with diabetes. FASEB J. 30, 601‐611 (2016). www.fasebj.org